Social and emotional difficulties among high ability students - Alencar, Eunice Soriano de (2008)
Social and emotional difficulties observed among highly able students are addressed. The asynchronous development, perfectionism, over-excitability, underachievement, and other social and emotional difficulties are discussed, describing factors related to them. The article finalizes highlighting possible contributions of the psychologist on counseling high ability students, their families and teachers, with the purpose of preventing or reducing maladjustments, as well as of helping them optimize their developmental process.